Disease Burden and Spectrum of Symptoms That Impact Quality of Life in Pediatric Patients With Eosinophilic Esophagitis - Mirna Chehade; Girish S. Hiremath; Noam Zevit; Salvatore Oliva; Tiffany Pela; Angela Khodzhayev; Juby Jacob-Nara; Amr Radwan (Gastro Hep Advances)
Eosinophilic esophagitis (EoE) is a progressive type 2 inflammatory disease characterized by symptoms related to esophageal dysfunction and significant esophageal eosinophilic infiltration. It can affect patients from infancy through adulthood. Pediatric EoE has a multidimensional impact on the quality of life of both patients and their families. Nonspecific symptoms mimicking other gastrointestinal conditions, such as food refusal, failure to thrive, and feeding difficulties, may profoundly affect young children’s eating skills, growth, and psychosocial status, as well as impact family financial conditions. In adolescence, dysphagia and esophageal food impactions often lead to feeding-related anxiety and influence social lives. Delays in diagnosis, arising from lack of awareness among families and clinicians and compensatory eating behaviors, could increase the risk of fibrostenotic complications, which may ultimately add to the symptom burden. Currently available treatment options include proton pump inhibitors, dietary therapies, swallowed topical steroids, esophageal dilation, and biologic therapy. Despite the efficacy of these approaches, disease burden may be further impacted by their limitations, including poor adherence rates, refractory disease, potential long-term safety concerns, and high costs for care. Thus, there is a need for more timely diagnosis in clinical practice and novel targeted disease-modifying therapies better tailored to treat various phenotypes of EoE, aimed at reducing the physical and psychosocial burdens on patients and their caregivers.